Intervensi pada Pasien Tuberkulosis untuk Meningkatkan Kepatuhan dan Manajemen Diri - Ratna Minggarwati; Neti Juniarti; Hartiah Haroen (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to design and analyze interventions that can be used in tuberculosis patients to improve adherence and self-management in preventing multi-drug-resistant tuberculosis (MDR-TB) events. The research method is a literature review conducted to analyze the concept of intervention in tuberculosis patients. A comprehensive literature search was carried out through an electronic database of CINAHL and PUBMED from publications from early 2020 to December 30, 2022. The results showed that interventions that could be carried out were increasing knowledge, increasing the role of medical staff in motivating and observing both through messages, text, or telephone, improving education through health promotion so that TB patients can comply with treatment, and improving self-management. Other interventions that can improve adherence to TB treatment are psychological counseling, individual education, digital-based medication monitoring (DOTS) WOT, telephone-based pill refill reminders, and medication monitoring), and peer support. In conclusion, good self-management behavior is proven to reduce the progression of diseases, including tuberculosis. Age, attitude, marital status, and home conditions influence self-management. While the knowledge factor indirectly affects self-management through mentality. Thus, knowledge and attitudes require the intervention of other parties who can mediate. This is to avoid the occurrence of Multidrug-Resistant Tuberculosis (MDR-TB). Keywords: Intervention, Compliance, Self Management, Tuberculosis